PENATALAKSANAAN FISIOTERAPI PADA KONDISI PLANTAR FACITIS SINISTRA DENGAN MODALITAS INFRA MERAH, ULTRASOUND, MASSAGE FRICTION DAN ACTIVE STRETCHING DI RSUD BENDAN KOTA PEKALONGAN - Istya Martya Afitha; Irine Dwitasari Wulandari (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Plantar fascitis is heel pain caused by inflammation or irritation of the plantar fascia. Plantar fascitis is characterized by complaints of pain in the heel during the first step in the morning, when walking pain is usually reduced. Signs and symptoms that arise in the condition of Plantar Facitis are the presence of tenderness, the presence of motion pain, the presence of oedem, a disturbance of functional activity (Assad et al, 2016).In this case the technology was chosen to overcome the above problems by using infra merah modalities, ultrasound, friction massage, active stretching . This research was conducted at Bendan Hospital in Pekalongan City with a descriptive analytic research design. The research subjects in Scientific Writing are patients with Plantar facitis conditions who will be given physiotherapy intervention with infra merah modalities, ultrasound, friction massage, active stretching . Methods of data collection and data analysis using the Autoanamnesis method. The research instrument consisted of examining Pain with VAS, spasm with palpation, edema with antopometry and Functional Activity Ability with the Foot Funtional Index.The results after the 1st treatment until the fourth therapy there was a decrease in pain from T1 silent pain 0, motion pain 3, tenderness 4 to T4 to silent pain 0, motion pain 1, tenderness 3, There was a decrease in muscle spasm from T1 = 1 to T4 becomes 0, there is a decrease in oedem from the left T1 25cm right 24cm to T4 becomes the left T1 24cm dektra 24cm. There is an increase in fungional activity in T3.The conclusion of this study is that the modalities of physiotherapy with infra merah, ultrasound, friction massage, active stretching  can help reduce the problems that arise in the condition of Plantar Facitis.